2022
DOI: 10.3389/fmolb.2022.846579
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Detection and Research on Screening Mutant Gene TTN of Moyamoya Disease Family Based on Whole Exome Sequencing

Abstract: Moyamoya disease (MMD) has a high incidence in Asian populations and demonstrates some degree of familial clustering. Whole-exome sequencing (WES) is useful in establishing key related genes in familial genetic diseases but is time-consuming and costly. Therefore, exploring a new method will be more effective for the diagnosis of MMD. We identified familial cohorts showing MMD susceptibility and performed WES on 5 affected individuals to identify susceptibility loci, which identified point mutation sites in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The TTN gene has a long coding sequence and mutations at any site may lead to abnormal myosin function, which will result in aberrant growth of muscle fibers ( Savarese et al, 2018 ). Numerous previous studies have found that TTN mutation is associated with diseases such as tibial muscular dystrophy ( Hackman et al, 2002 ), moyamoya disease ( Xiao et al, 2022 ) and familial atrioventricular block ( Liu et al, 2020 ). However, recently scholars have focused on the relationship between TTN mutation and immunotherapy for solid tumors ( Miao et al, 2018 ; Jia et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The TTN gene has a long coding sequence and mutations at any site may lead to abnormal myosin function, which will result in aberrant growth of muscle fibers ( Savarese et al, 2018 ). Numerous previous studies have found that TTN mutation is associated with diseases such as tibial muscular dystrophy ( Hackman et al, 2002 ), moyamoya disease ( Xiao et al, 2022 ) and familial atrioventricular block ( Liu et al, 2020 ). However, recently scholars have focused on the relationship between TTN mutation and immunotherapy for solid tumors ( Miao et al, 2018 ; Jia et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%